2013
DOI: 10.1097/mpa.0b013e31827a7b01
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound in the Differential Diagnosis of Exocrine Versus Neuroendocrine Pancreatic Tumors

Abstract: Contrast-enhanced ultrasound has a valuable diagnostic accuracy in differentiating exocrine from endocrine pancreatic tumors, which is a fundamental step to address appropriate histological evaluation, therapeutic approach, and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In the present study, the accuracy of CEUS in characterizing hyperenhancing lesions was 72.8%, similar to the one published by Serra et al [23] -73.8%; but slightly lower than in the PAMUS, in which the accuracy was 90.5% [3]. This might be due to the small number of hyperenhancing lesions identified by CE-CT/MRI (28 cases) and also because we couldn't verify the imaging results with a more sensitive method (pathology).…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, the accuracy of CEUS in characterizing hyperenhancing lesions was 72.8%, similar to the one published by Serra et al [23] -73.8%; but slightly lower than in the PAMUS, in which the accuracy was 90.5% [3]. This might be due to the small number of hyperenhancing lesions identified by CE-CT/MRI (28 cases) and also because we couldn't verify the imaging results with a more sensitive method (pathology).…”
Section: Discussionsupporting
confidence: 79%
“…Although relatively new for the pancreatic evaluation, CEUS represents a safe and feasible technique to immediately better characterize and stage the disease during single US examination [33]. Our review found few studies investigating the vascular pattern of pathologically proven pancreatic tumors and enrolling more than 100 patients [1, 11,12,15,20,26,28]. However, during the last ten years we observed a progressive increase in published papers regarding CEUS of the pancreas.…”
Section: Methodological Qualitymentioning
confidence: 76%
“…In the Pancreatic Multicenter Ultrasound Study (PAMUS) meta-analysis, a high accuracy of CEUS in characterizing pancreatic masses was reported, as solid pancreatic lesions were correctly characterized in respect to pathology with an accuracy of 91.7% and pancreatic ductal adenocarcinoma was correctly characterized with an accuracy of 87.8% [70]. In the literature, a specificity close to 100% for transabdominal CEUS diagnosis of ductal adenocarcinoma, with a sensitivity of 90%, has been reported [71,72]. Recently, a metaanalysis was conducted with the aim of evaluating the role of CEUS in differentiating among pancreatic lesions.…”
Section: Pancreasmentioning
confidence: 99%